PI3K inhibition modulates PON gene expression and disrupts survival pathways in retinoblastoma Y-79 cells - Ramya Ravi; Sathik Shajahan; Jayavigneeswari Suresh babu; S. R. Bharathi devi (Molecular Biology Reports, 2026)

Studies on the immunological biomarkers of bovine tuberculosis in naturally infected cattle - Shalini Sharma; Gursimran Filia; Geeta Devi Leishangthem; R S Sethi; Gurpreet Kaur (Brazilian Journal of Microbiology, 2026)

Green zinc oxide nanoparticles from Tagetes erecta (L.) leaves reduce Meloidogyne incognita-induced stress in Solanum lycopersicum (L.) - Thangavel Manimegalai; S. Iruthaya Kalai Selvam; Lakshmanan Archana Devi; D. Kasthuri Santira Kumari (Physiological and Molecular Plant Pathology, 2026)

Genetic Divergence and Biogeographic Patterns in the Deep-Sea Shrimp Plesionika semilaevis Across the Western Indian Ocean - S. Sreelakshmy; Shijin Ameri; Rekha Devi Chakraborty; P. Laxmilatha; Shubhadeep Ghosh (Thalassas: An International Journal of Marine Sciences, 2026)

A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Submergence Tolerance in Rice: Genetic Mechanisms, Physiological Adaptations, and Breeding Strategies of Flood Resilience - S. Manju Devi; S. Vignesh; A. John Joel; M. Raveendran; R. Pushpa; R. Suresh (Plant Molecular Biology Reporter, 2026)

Performance Evaluation of EOS-06 OCM-3 Chlorophyll-a Retrievals in Case-1 Waters - Chiranjivi Jayaram; Neethu Chacko; Rajdeep Roy; T. Devi Varaprasada Rao; P. V. Nagamani; T. V. S. Udaya Bhaskar; K. N. Babu; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Trade-offs and Synergies of Soil Restoration Through Conservation Tillage: Strategies for Sustainable Agri-Food Systems in Riverine Agroecosystems - S. Pazhanisamy; Rodda Chandana Devi; Sunita Kumari Meena; E. Rathinaguru; R. Sushma Devi; S. Mala; Dinesh Jinger; Raj Kumar Jat; H. S. Jat; Vijay Singh Meena; M. L. Jat (Anthropocene Science, 2026)

Microplastics and chemical contaminants of polymers in cage-cultured fish: A pioneering case study from Ashtamudi Ramsar Lake, India - Suvarna S. Devi; Arushi Thaikkattu Pushpan; Anakha Saji; Krishnannair Satheesh Kumar; Appukuttannair Biju Kumar (Estuarine, Coastal and Shelf Science, 2026)

Assessment of bioactive compounds, antioxidant pigments and mineral diversity in leaves of amaranth (Amaranthus spp.) genotypes - Ajay Kumar Sharma; Vidya Sagar; Jyoti Devi; S. V. Dwivedi; Neetu; Vishal Chugh; Ashutosh Rai; Anurag; Nakul Gupta; Rajesh Kumar; N. Rai; T. K. Behera (Genetic Resources and Crop Evolution, 2026)

Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Metabologenomic approach to discover aromatic polyketides, angucycline antimicrobial compounds produced by alkaliphilic Streptomyces - Shalini Devi S.; Sreenivasulu Y.; Prakruti K. (Natural Product Research, 2026)

Association studies of stem characteristics and cell wall polymers for genetic enhancement of lodging resistance in rice - Kavya Zoopally; Jyothi Badri; Radhika Kommineni; Sanjeeva Rao Durbha; Akshay Mamidi; Kamala Devi Datla; Padmashree Revadi; Harshavardhan Rayudu Jamedar; S. V. Sai Prasad; Raman Meenakshi Sundaram (Journal of Plant Biochemistry and Biotechnology, 2026)

Design, and Synthesis of Donor–π–Acceptor (D–π–A) Heterocyclic Compounds Exhibiting Aggregation-Induced Emission (AIE/AIEE) and Solid-State Emission - Thangjam Linda Devi; Mayanglambam Maneeta Devi; Francis A. S. Chipem; Okram Mukherjee Singh (Journal of Fluorescence, 2026)

Development and piloting of the rural water supply climate-resilience monitoring tool (RWS-CRMT) - D. Daniel; Adhin Harum Wulaningtyas; S. Satriani; Elsa Febriana Devi; Cindy Priadi; D. Danisha; Rioneli Ghaudenson; Sucipta Laksono; Juliet Willetts (Climate and Development, 2026)

Comprehensive Analysis of Water Contamination in IoT-Enabled Aquaculture Systems Using Advanced Quantum Optical Convolutional Neural Network Techniques for Enhanced Environmental Monitoring - S Janarthanan; S Shanthini Devi; M Monica Dhana Ranjini; Raghul G (Water Resources Management, 2026)

Planthopper-induced vulnerability: amplifying fall armyworm, Spodoptera frugiperda (J.E. Smith) preference in rice - V. Chinna Babu Naik; S. Rakhesh; D. Devi Pratyusha; K. A. V. Sindhura; Kokkula Akhilesh; K. Vani Sree; R. M. Sundaram (Phytoparasitica, 2026)

Septic Shock Inhibition by Targeting IRAK-4 - Deepali Shrivastava; Dikshita Panwar; Lavleen Kumar Gupta; Y. Adinarayana Reddy; Anjani Devi Chintagunta; N. S. Sampath Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Advanced Photocatalytic Decomposition Using TiO₂ Nanorods: Optimization Through Factorial Modeling - S. K. Thiyakarajan; S. Vijayakumar; B. Akash; D. Devadharshini; V. Devi Rajeswari; V. Yamini (Nanotechnology for Environmental Engineering, 2026)

Application of bioencapsulated microalgae in marine cladoceran (Penilia sp.) for enhancing growth and improve production of Asian seabass (Lates calcarifer) - K. Nanthini Devi; P. Santhanam; A. Shenbaga Devi; P. Raju; R. Sagaya Princy; K. Rajagopal; I. S. Bright Singh; A. S. Sahul Hameed; A. Jishnu Panamoly; P. Perumal (Journal of Applied Phycology, 2026)

Characterization of Genetic Diversity in Amaranthus Species Using Morpho-Molecular Markers - Ajay Kumar Sharma; Vidya Sagar; S. V. Dwivedi; Jyoti Devi; Neetu; Shailesh K. Tiwari; Sunil K. Singh; N. Rai; Rajesh Kumar; T. K. Behera (Indian Journal of Genetics and Plant Breeding, 2026)

Integrated profiling of drought tolerant rice landraces through comprehensive examination of gene expression, morpho-physiological traits, and biochemical responses during reproductive stage - P. Dharani; T. Nivethitha; S. Manju Devi; A. John Joel (Cereal Research Communications, 2026)

Whole-genome sequencing and functional characterization of a heterocystous cyanobacterium promoting rice seed germination - Nachu Nikhil Sai; N. S. Sampath Kumar; Anjani Devi Chintagunta (World Journal of Microbiology and Biotechnology, 2026)

Green way aqueous extraction of Corbichonia decumbens leaves procured from Kolli hills, Tamil Nadu, India, and investigation of their various biological activities - Gayathri Ramalingam; Ashwini Devi Balaraman; Poojasri Sribal; Meenakumari S; Arjun Chandra Balaji B; Chamundeeswari M; Sathiya Gunasekaran; Andrew Charles; Venkatesan D; Rubalakshmi G (Natural Product Research, 2026)

Unveiling the prevalence, pathogenic and molecular characterization of Xanthomonas strains responsible for bacterial leaf spot of tomato and pepper in India - P. Lokesh Babu; V. Devappa; J. Rajender; Neelam Geat; R. S. Devi; Rahul Patidar; Ainmisha Singh; V. K. Banarwal; Jasdeep Chatrath Padaria; Anju Kamra; Dinesh Singh (Journal of Plant Pathology, 2026)

Novel hybrid slag blend as a sustainable production & development in SCC - Selesca Devi Selvaraj; S. Sruthimira; S.S. Vivek (Innovative Infrastructure Solutions, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Integrated subsurface drip fertigation and residue management enhance maize resource-use efficiency in semi-arid agro-ecosystems - Arjun Singh; Anchal Dass; S. Sudhishri; V.K. Singh; Prameela Krishnan; Pravin K. Upadhyay; K. Shekhawat; R.N. Sahoo; S.S. Rathore; Ayekpam Dollina Devi; A.R. Devika (Field Crops Research, 2026)

Utilization of crop wild relatives in genetic improvement of bitter gourd, Momordica charantia L. - S. Devi; R. Neelavathi; C. Indu Rani; R. Kalaiyarasi; K. Gurusamy (Genetic Resources and Crop Evolution, 2026)

Sustainable fabrication of TiO2 nanoparticles using Gracilaria edulis extract: a study on biofilm inhibition and photocatalytic industrial dye degradation - Sivakumar Murugesan; Sumathy Rengarajan; Alagendran Subbarayalu; Sukirtha Raman; Renuga Devi Navaneethan; Sahaya Sathish S; Raja Rajeshwari G; Arjun Pandian; Bharathiraja Chinnapandi (Environmental Geochemistry and Health, 2026)

Unraveling genetic diversity in cowpea (Vigna unguiculata (L.) Walp.) for yield and yield attributing traits through multivariate analysis - S. Manju Devi; P. Jayamani (Vegetos, 2026)

RSM-ANN-GA framework for predictive modeling and optimization of sonocatalytic eosin dye degradation using ZnO@SiO2 nanocomposites - G.V. Aatral; V. Chitra Devi; S. Mothil; R. Sathish Raam (Journal of Contaminant Hydrology, 2026)

Bioconversion of agricultural waste into bacterial single-cell protein: recent advances and modelling approaches - Sharda Devi Rajput; Neha Pandey; S. Keshavkant (Systems Microbiology and Biomanufacturing, 2026)

Subsurface drip fertigation optimizes nitrogen distribution in soil under maize cultivation - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; R. N. Sahoo; Kapila Shekhawat; Pravin K. Upadhyay; S. S. Rathore; Ayekpam Dollina Devi (Plant and Soil, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Exploring myricetin: A comprehensive review of its pharmacological potential, formulation strategies, and clinical outlook - Amita Devi; Atul Kabra; Abdulaziz S. Saeedan; Mohd Nazam Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sustainable Approach for Oil Spill Cleanup Using Waste Coconut Husk-Based Oleophilic Nanogels - Kavita Devi; Kiran Kumar; Ghanshyam S. Chauhan; Sandeep Chauhan; Anamika Ramchaik (International Journal of Environmental Research, 2026)

Evaluation of CMIP6 multi-model ensemble for assessing the intensity and duration of Indian monsoon under future warming scenarios - Smrutishree Lenka; Krushna Chandra Gouda; Rani Devi; T. S. Mohan (Climate Dynamics, 2026)

Integrated Nutrient Management: An Effective Strategy to Mitigate Greenhouse Gas Emission and Global Warming Potential Under Rice Cultivation - Naorem Twinkle Devi; Angom Sarjubala Devi; R. S. Khoiyangbam (Agricultural Research, 2026)

Conservation agriculture for riverine agri-food systems under the climate crisis: enhancing soil health and mitigating erosion - Pazhanisamy S.; Devendra Singh; Rodda Chandana Devi; Vijay Singh Meena; Sunil Kumar; R.S. Singh; S.S. Prasad; R. Sushma Devi; Jogdande Sai Prasad; K. Damodar; Abhinandan Singh; V. Sridevi; et al. (Soil and Tillage Research, 2026)

Ingenious design and application of ZnAl-LDH/BiOBr Z-scheme heterojunction for effective photocatalytic degradation of tetracycline in aqueous environment: Insight into mechanism and toxicity estimation - R. Janani; M. Kanagalakshmi; S. Gopika Devi; Anitha Pius (Process Safety and Environmental Protection, 2026)

Edible synbiotic film based on soy protein reinforced with nanocellulose synthesized from jackfruit residues and probiotic (Lactobacillus pentosus) for feta cheese packaging - B. Pooja; R. Preetha; V. Sreejit; S. Maanila Devi (Food Bioscience, 2026)

Exploring the microbial basis of postbiotic and paraprobiotic therapy in ulcerative colitis - N. Pavithra; M. Devi; S. Nirenjen; B. Keerthana; V. K. Giresh kumar; R. Yogalakshmi; M. G. Priyadharshni; N. Harikrishnan (Archives of Microbiology, 2026)

Traditional, Nutritional, and Ayurvedic Perspectives on Millets: Reclaiming their Role in Modern Diets - Anil Kumar Kakani; Kanaka Durga Devi Nelluri; Sahithi Kamepalli; Alaparthi Bhavana; Padamata Sai Rohith; Surapaneni U. S. Sai Tejaswini (Current Pharmacology Reports, 2025)

Bio-inspired synthesis of copper oxide and silver-doped copper oxide nanoparticles: Investigating their electrochemical and antibacterial properties - N.L. Sheeba; L. Renuga Devi; S. Kamatchi Devi; S.C. Vella Durai; S. Meenakshi Sundar (Next Research, 2025)

Comparative Flood Risk Mapping Using Knowledge-Driven, Data-Driven, and Ensemble Models in a Humid Tropical River Basin in India - Chandini Padmanabha Panicker Chandr Senan; Rajendran Shobha Ajin; B. R. Anaswara Devi; A. Rajaneesh; Jitendra K. Nagar; K. S. Sajinkumar (Water Conservation Science and Engineering, 2025)

Growth performance, gut health, and toxicity effects of feeding broiler chickens diets with graded levels of coffee by-products - Agnus Achari; Ashika Devi; Sharon S. Gaundan; Abubakar Danmaigoro; Archibold G. Bakare (Tropical Animal Health and Production, 2025)

Identification and Characterization of Phosphorus Deficiency Tolerant Rice Genotypes in North-Eastern India - Y. Sanatombi Devi; Th.Seileshkumar Singh; E. Lamalakshmi Devi; Philanim W. S.; Somnath Roy; Amit Kumar; Pramesh Devanna; Awadhesh Kumar; T. Basanta Singh; Kh.Rishikanta Singh; Akoijam Ratankumar Singh; Ramgopal Laha; et al. (Tropical Plant Biology, 2025)

Harnessing IDO inhibitors to optimize cancer immunotherapy - Safia Obaidur Rab; Huda K. Jaafar; Majid S. Jabir; H. Malathi; Seema Devi; Atreyi Pramanik; Hussein Riyadh Abdul Kareem Al-Hetty; Mohammed Jawad Alnajar; Sabrean F. Jawad; Yasser Fakri Mustafa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular, genetic and biochemical strategies: rice’s arsenal against gall midge - S. Devi Nandana; S. Jeyarani; Chellappan Gopalakrishnan; Loganathan Arul; Sheela Venugopal; Jegadeesan Ramalingam (Molecular Biology Reports, 2025)

Transmission dynamics and localization of tomato leaf curl New Delhi virus in cucurbits via sweet potato whitefly, Bemisia tabaci (Gennadius) - Kathiresan Sivagnanapazham; Gandhi Karthikeyan; Shanmugasundram Pavithran; Sankarasubramanian Harish; Marimuthu Murugan; T. K. S. Latha; Harinarayanan Usha Nandhini Devi (Molecular Biology Reports, 2025)

Cognitive neurodynamic approaches to adaptive signal processing in wireless sensor networks - K. G. Shanthi; A. Mary Joy Kinol; S. Rukmani Devi; K. Kannan (Cognitive Neurodynamics, 2025)

Foliar Application of Nano-ZnO Improves Growth, Yield, Quality, and Leaf Nutrient Status of Strawberry Over Conventional Zinc Sulfate - Monika S.; Nilesh Bhowmick; Aditi Chakraborty; Mutum Preema Devi; Abhas Kumar Sinha; Sankalpa Ojha; Soumen Maitra; Binayak Chakraborty (Applied Fruit Science, 2025)

Exploring blue carbon research in India: current landscape and future avenues - Sibin Antony; Karthikeyan Perumal; Suvarna S. Devi; Shahin Shajahan; Appukuttannair Biju Kumar (Marine Pollution Bulletin, 2025)

Real-time earthquake magnitude estimation utilizing a mixed dataset set of observed and simulated P-wave onsets for the Kumaon Himalaya from Mw3.0–7.5 earthquakes - Suraj Kumar Pal; S. Devi; Sandeep; P. Kumar; A. Joshi; Monika; R. Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

In-silico insights into Terminalia citrina targeting OmpA: an approach to combat multidrug resistance in Acinetobacter baumannii - Romen Meitei Lourembam; Jobina Rajkumari; Arunkumar Singh Koijam; Sushmita Bhattacharya; Sulagna Basu; Sunil S. Thorat; Sarangthem Indira Devi (In Silico Pharmacology, 2025)

Comprehensive review of leonurine: harnessing its therapeutic potential for chronic diseases - Mukesh Kumar Manickasamy; Uzini Devi Daimary; Anjana Sajeev; Mohamed Abbas; Mohammed S. Alqahtani; Ayman Abdulhammed; Ajaikumar B. Kunnumakkara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Targeting EZH2 in autoimmune diseases: unraveling epigenetic regulation and therapeutic potential - Hashem Ahmed Abu Harirah; Mohammed Hashim Mohammed; Sami Ahmed Zaher Basha; Subasini Uthirapathy; Subbulakshmi Ganesan; Aman Shankhyan; Girish Chandra Sharma; Anita Devi; Abed J. Kadhim; Naher H. S. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Compositional characterisation of colostrum and proline rich polypeptides of indigenous cattle (Bos indicus family) and Holstein Friesian (Bos taurus) and their crossbred Karan Fries cattle - Mamta Kumari; Usha Devi; T.M. Amrutha; N. Sandeep; M.H. Sathish Kumar; Suman Kapila; Abdul S. Hussain; C.T. Manoj Kumar (International Dairy Journal, 2025)

Response of foxtail orchid (Rhynchostylis retusa L. Blume.) restoration on various hosts in East Siang district, Arunachal Pradesh - Ruchika Borbaruah; Preeti Hatibarua; Arunkumar Phurailatpam; Sunil Kumar; N. Surmina Devi; Prashant Kisan Nimbolkar; A. S. Mailappa (Plant Ecology, 2025)

Utilization of genetic diversity and marker trait association to improve anaerobic germination tolerance in rice (Oryza sativa L.)‏ - S. Manju Devi; A. John Joel; M. Raveendran; R. Pushpam; S. Muthuramu; R. Pushpa; N. Sritharan; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Clinical spectrum of AES (Acute encephalitis syndrome) and a syndromic approach for its diagnosis - Sidharth S; Sarada Devi K L; Sreelatha K H (Journal of NeuroVirology, 2025)

Carbon dioxide sequestration and Single-Cell protein Production: Opportunities and challenges in circular economy - Sharda Devi Rajput; S. Keshavkant (Chemical Engineering Journal, 2025)

Fabrication of CoTe-phosphorus doped g-C3N4 photocatalytic engine: A leap towards eco-friendly hydrogen production - V. Bharathi Mohan; S. Jayachitra; P. Devi; P. Murugan; M. Sathish (Chemical Engineering Journal, 2025)

Comparative analysis of carbon sequestration potential in different wetland ecosystems: insights from phumdi-dominated wetlands of Northeast India - S. Gojendro Singh; Sanjay Kumar Das; Vidya Shree Bharti; Ch. Basudha Devi; Subir Kumar Nag; Ph. Menaka Sharma; Chandan Debnath (Environmental Monitoring and Assessment, 2025)

Phosphate-solubilizing microorganisms for sustainable phosphorus management in rice - S. Ahash; K. Manikandan; T. Sivasankari Devi; S. Elamathi; S. Maragatham; K. Subrahmaniyan (Rhizosphere, 2025)

Whole Genome Sequencing of Carbapenem-Resistant Enterobacter hormaechei Isolated from Thiruvananthapuram, Kerala (India) - Parvathi Vaikkathillam; Praveen Kumar; S. Manjusree; Minsa Mini; Devi Jayakumar; Amjesh Revikumar (Indian Journal of Microbiology, 2025)

Production and Extraction of Red Bioactive Pigment from Streptomyces griseorubiginosus and Formulation of Bio-Lip Balm - S. Vignesh; P. M. Anandu; G. S. Gopuraj Varrier; Nikhil Brijmohan; G. Gokula Krishnan; Sanjeev K. Ganesh; Sreelakshmi R. Nair; V. Mohanasrinivasan; C. Subathra Devi (Indian Journal of Microbiology, 2025)

Insecticidal Potential of Essential Oil and Sesquiterpene Alcohols from Leaves of Clausena indica (Dalz.) Oliver Against Spodoptera litura, Helicoverpa armigera, and Tribolium castaneum Under Laboratory and Field Conditions - J. Achyutha Devi; R. Thangapandian; C. Vijayaraghavan; Raja Rama Devi Patel; S. Ravi Kiran (Neotropical Entomology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluating geostatisical approaches and their integration with pedotransfer functions for estimating the spatial distribution of cation exchange capacity - Farag M. A. Altalbawy; Merwa Alhadrawi; Ashok Kumar Bishoyi; Subbulakshmi Ganesan; Aman Shankhyan; S. Sunitha; Anita Devi; Rajashree Panigrahi; Rubyat Alam (Environmental Monitoring and Assessment, 2025)

Unveiling the interaction, cytotoxicity and antibacterial potential of pyridine derivatives: an experimental and theoretical approach with bovine serum albumin - Rosalin Das; Patitapaban Mohanty; Pragyan P. Dash; Swagatika Mishra; Ajit K. Bishoyi; Lokanath Mishra; Laxmipriya Prusty; Devi P. Behera; Debasmita Dubey; Monalisa Mishra; Harekrushna Sahoo; Mohd S. Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spatiotemporal Changes of Pollutant Concentrations in South India during COVID-19 Lockdown Using Ground and Satellite-based data: a Comparative Analysis from the Machine Learning Model - Pelati Althaf; Nulu S. M. P. Latha Devi; Kanike Raghavendra Kumar (Water, Air, & Soil Pollution, 2025)

Photodegradation of methylene blue from waste water under visible light and bacterial growth inhibition by GO and rGO blended CdO: Mn nanoparticles– a comparative study - N. Manjula; A. R. Balu; B. Sowmiya Devi; S. Chitra Devi; K. Devendran; M. Sriramraj; S. Adityan; A. Vinith (Nanotechnology for Environmental Engineering, 2025)

Efficiency assessment of EV system integrated with solar PV based SRM using hybrid approach - B. Devi; S. Edwin Jose (Environment, Development and Sustainability, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Remote Sensing Analysis of the LIDAR Drone Mapping System for Detecting Damages to Buildings, Roads, and Bridges Using the Faster CNN Method - S. Meivel; K. Indira Devi; A. Sankara Subramanian; G. Kalaiarasi (Journal of the Indian Society of Remote Sensing, 2025)

Recent advances in various cleaning strategies to control membrane fouling: a comprehensive review - Devi Sri Rajendran; Eggoni Gayathri Devi; V. S. Subikshaa; Purvi Sethi; Atharva Patil; Anasuya Chakraborty; Swethaa Venkataraman; Vaidyanathan Vinoth Kumar (Clean Technologies and Environmental Policy, 2025)

Innovative Approaches in Regulatory Affairs: Leveraging Artificial Intelligence and Machine Learning for Efficient Compliance and Decision-Making - C. S. Ajmal; Sravani Yerram; V. Abishek; V. P. Muhammed Nizam; Gayatri Aglave; Jayasri Devi Patnam; Rajeev Singh Raghuvanshi; Saurabh Srivastava (The AAPS Journal, 2025)

Correction: Isoptericola haloaureus sp. nov., a dimorphic actinobacterium isolated from mangrove sediments of southeast India, implicating biosaline agricultural significance through nitrogen fixation and salt tolerance genes - Munisamy Prathaban; Ragothaman Prathiviraj; Mythili Ravichandran; Sharmila Devi Natarajan; Murugesan Sobanaa; S. Hari Krishna Kumar; Varadharaju Chandrasekar; Joseph Selvin (Antonie van Leeuwenhoek, 2025)

Study of Photoluminescence and Thermoluminescence Properties of Tb3+ Doped Green Emitting YPO4 Nanophosphors - Khundrakpam Chanchan Devi; Ritesh Hemam; S. Dorendrajit Singh (Journal of Fluorescence, 2024)

The state of marine debris and microplastic research in India: Bridging knowledge gaps for robust marine litter policy - Karthikeyan Perumal; Suvarna S. Devi; Kurian Mathew Abraham; Appukuttannair Biju Kumar (Ocean & Coastal Management, 2024)

Retraction notice to “Hydrolysis of biomass using a reusable solid carbon acid catalyst and fermentation of the catalytic hydrolysate to ethanol” [Bioresour. Technol. 188 (2015) 99–102] - Mandavi Goswami; S. Meena; S. Navatha; K.N. Prasanna Rani; Ashok Pandey; Rajeev Kumar Sukumaran; R.B.N. Prasad; B.L.A. Prabhavathi Devi (Bioresource Technology, 2024)

Decoding the genetic influence of CT60 non-coding polymorphism in CTLA-4 gene and sCTLA-4 biomarker with rheumatoid arthritis in the Indian population - V. Shamala; S. Asha Devi (Molecular Biology Reports, 2024)

Optimization strategies for enhanced production of single cell protein: recent advances and perspectives - Sharda Devi Rajput; Neha Pandey; S. Keshavkant (Reviews in Environmental Science and Bio/Technology, 2024)

Isoptericola haloaureus sp. nov., a dimorphic actinobacterium isolated from mangrove sediments of southeast India, implicating biosaline agricultural significance through nitrogen fixation and salt tolerance genes - Munisamy Prathaban; Ragothaman Prathiviraj; Mythili Ravichandran; Sharmila Devi Natarajan; Murugesan Sobanaa; S. Hari Krishna Kumar; Varadharaju Chandrasekar; Joseph Selvin (Antonie van Leeuwenhoek, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Microplastic assessment in aquaculture feeds: Analyzing polymer variability across commercial fishfeeds from three continents - Suvarna S. Devi; Shilpa Jayan; Appukuttannair Biju Kumar (Journal of Hazardous Materials, 2024)

Harmony in nature's elixir: a comprehensive exploration of ethanol and nano-formulated extracts from Passiflora incarnata leaves: unveiling in vitro cytotoxicity, acute and sub-acute toxicity profiles in Swiss albino mice - Balasubramanian Deepika; Pemula Gowtham; Vijayashree Raghavan; Jane Betsy Isaac; Sobita Devi; Venkatakrishnan Kiran; Devadass Jessy Mercy; P. S. Sharon Sofini; A. Harini; Agnishwar Girigoswami; Koyeli Girigoswami (Journal of Molecular Histology, 2024)

Investigation of radioactivity and heavy metal levels in soil samples from neutral and vegetation land of Punjab, India - Sanjeet S. Kaintura; Swati Thakur; Sarabjot Kaur; Soni Devi; Katyayni Tiwari; Priyanka; Arzoo Sharma; Pushpendra P. Singh (Environmental Monitoring and Assessment, 2024)

Synthesis, Structural, Spectroscopic, Fluorescence, and Dielectric Studies of Bis-(4-Aminopyridine)-Zinc(II) Acetate: A Metal–Organic Crystal - Helen Merina Albert; R. Priya; Bajirao Bhila Ahire; N. S. M. P. Latha Devi; J. Madhuri Sailaja; S. Raziya Tabassum; Nellore Manoj Kumar; C. Alosious Gonsago (Journal of Fluorescence, 2024)

Integrating computational models and machine learning for corrugated absorber plate solar collector thermal predictions - Madhankumar S.; Devi Ilangovan; Karthickeyan Viswanathan (Process Safety and Environmental Protection, 2024)

Proactive Approaches to cGMP Compliance: Insights and Key Takeaways from USFDA Warning Letters to Pharmaceutical Industries Between 2019 and 2024 - Gayatri Aglave; Sravani Yerram; Jayasri Devi Patnam; C. S. Ajmal; V. P. Muhammad Nizam; Ramesh Joga; Rajeev Singh Raghuvanshi; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2024)

Energy management of slow and fast charge electric vehicles (EV) in smart parking lot using NBO-THDCNN algorithm - B. Devi; S. Edwin Jose (Environment, Development and Sustainability, 2024)

Potato Yield Classification Using Weather Variables: a Discriminant Analysis Approach - S. R. Krishna Priya; N. Naranammal; Walid Emam; Yusra Tashkandy; Monika Devi; Pradeep Mishra (Potato Research, 2024)

Does the microplastics ingestion patterns and polymer composition vary across the oceanic zones? A case study from the Indian coast - Suvarna S. Devi; Nasila Saifudeen; Krishnannair Satheesh Kumar; Appukuttannair Biju Kumar (Marine Pollution Bulletin, 2024)

Attention module incorporated transfer learning empowered deep learning-based models for classification of phenotypically similar tropical cattle breeds (Bos indicus) - Radhika Warhade; Indu Devi; Naseeb Singh; Shruti Arya; K. Dudi; S. S. Lathwal; Divyanshu Singh Tomar (Tropical Animal Health and Production, 2024)

Racial diversity in Uromyces appendiculatus causing French bean rust - Banita Devi; Gurvinder Singh; Satish K. Gupta; Pramod Prasad; S. C. Bhardwaj; Vinaykumar Rachappanavar (Indian Phytopathology, 2024)

Microplastic contamination in Ashtamudi Lake, India: Insights from a Ramsar wetland - Suvarna S. Devi; Beena Ramachandran Gouri; S. Anjali; Appukuttannair Biju Kumar (Journal of Contaminant Hydrology, 2024)

Evaluating implementation of NCCN guideline-directed genetic screening recommendations for patients with pancreatic ductal adenocarcinoma - Aditya K. Ghosh; Sheena Bhushan; Oluseyi Abidoye; Shane S. Robinson; Ania Izabela Rynarzewska; Devi Sampat (Cancer Causes & Control, 2024)

Factors regulating proliferation and co-occurrence of loricate ciliates in the microzooplankton community from the eastern Arabian Sea - C. R. Asha Devi; Jhimli Mondal; N. N. S. Vishnu; C. K. Sherin; K. J. Albin; I. Anandavelu; G. V. M. Gupta (Aquatic Sciences, 2024)

Microtubules assembly inhibitors in combination with PPO, ACCase and ALS inhibitors herbicides for the management of multiple herbicide-resistant Phalaris minor in wheat under Indo-Gangetic Plains: a threat to sustainable wheat production - Sushil Kumar; R. S. Dadarwal; Todar Mal; Akshit; Priyanka Devi; Pardeep Kumar; Bhupesh Dhaka (Acta Physiologiae Plantarum, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

An investigation on the distribution dynamics of kiddi prawn, Parapenaeopsis stylifera (H. Milne Edwards, 1837) along southwest coast of India, using multi-dimensional approach - Dineshbabu A.P.; Maheswarudu G.; Josileen Jose; Lakshmi Pillai S.; Chakraborty Rekha Devi; Jinesh P.T.; Ragesh N.; Sreesanth L.; Shailaja Salian; Akash S.; Ratheeshkumar R.; Zacharia P.U.; et al. (Regional Studies in Marine Science, 2024)

Knockout of ecdysis triggering hormone receptor (ETHr) gene adversely affects the nymphal molting and adult reproduction in Bemisia tabaci - S. Karthigai Devi; Geetika Banta; Vikas Jindal (Pesticide Biochemistry and Physiology, 2024)

Evaluating the performance of electrocoagulation system in the removal of polystyrene microplastics from water - Akhila Subair; Priya K L; Suchith Chellappan; Thamanna Rahuman A; J. Hridya; P.S. Devi; Mariyam Salkka S; M.S. Indu; Arivalagan Pugazhendhi; Chingakham Chinglenthoiba (Environmental Research, 2024)

Study of iron-based metal–organic framework for selenite removal from water - V. Sharma; P. Borah; S. S. Bhinder; S. K. Kansal; P. Devi (International Journal of Environmental Science and Technology, 2024)

Exploring the taxonomic classification of Curvularia genera: Enhancing understanding of phytopathogenic species in Poaceae through morphological and molecular approaches - Dama Ram; Thokala Prameela Devi; Prasanna S. Koti; Bettanayaka Jeevan; Deeba Kamil; Chandra Sekhar Vanapalli; Shivappa Raghu; Sunil Kumar Sunani; Abhijeet Shankar Kashyap (Journal of Plant Pathology, 2024)

Native bio-control agents from the rice fields of Telangana, India: characterization and unveiling the potential against stem rot and false smut diseases of rice - Sowmya Vanama; N. S. Raja Gopalan; Maruthi Pesari; M. Baskar; Uma Devi Gali; D. Ladha Lakshmi; P. Koteshwar; G. Jesudasu; Santosha Rathod; M. Srinivas Prasad; Rajanikanth Panuganti; R. M. Sundaram; et al. (World Journal of Microbiology and Biotechnology, 2024)

Centella asiatica Leaf Extract Mediated One-Pot Green Synthesized rGO Decorated PbS/CdO Nanocomposite for Catalytic Degradation of Methyl Violet from Wastewater and Resistance Against Bacillus subtilis and Pseudomonas aeruginosa Bacterial Strains - M. Suganya; A. R. Balu; S. Chitra Devi; K. Usharani; M. Sriramraj; K. Devendran; S. Adityan (Water, Air, & Soil Pollution, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Ag decorated Zn-Al layered double hydroxide for adsorptive removal of heavy metals and antimicrobial activity: Numerical investigations, statistical analysis and kinetic studies - P.K. Asha; K. Deepak; M.K. Prashanth; L. Parashuram; V.S. Anusuya Devi; S. Archana; H. Shanavaz; S. Shashidhar; K.N. Prashanth; K. Yogesh Kumar; M.S. Raghu (Environmental Nanotechnology, Monitoring & Management, 2023)

Screening and validation of Ty-1, Ty-3 and Ty-3a specific markers in Solanum chilense accessions for resistance to tomato leaf curl virus - Muthukumar Palanisamy; Gograj Singh Jat; Pritam Kalia; Chitra Devi Pandey; Selvakumar Raman; Shilpi Kumari; Sachin Kumar; B. S. Tomar (Genetic Resources and Crop Evolution, 2023)

Residual Pattern of Chlorantraniliprole, Thiamethoxam, Flubendiamide and Deltamethrin in Tomato Fruit and Soil - Romila Akoijam; Arati Ningombam; Aruna Beemrote; S. S. Roy; Chongtham Sonia; Ch. Premabati Devi; A. Ratankumar Singh; Telem Ratan Singh; H. Nandakumar Singh; Chinglemba Hanglem; I. M. Singh (Bulletin of Environmental Contamination and Toxicology, 2023)

Antibiofilm potential of gallic acid against Klebsiella pneumoniae and Enterobacter hormaechei : in-vitro and in-silico analysis - Pooja P. Rajan; Praveen Kumar; Minsa Mini; Devi Jayakumar; Parvathi Vaikkathillam; Sneha Asha; Aparna Mohan; Manjusree S (Biofouling, 2023)

A comprehensive review on current trends and development of biomethane production from food waste: Circular economy and techno economic analysis - M. Keerthana Devi; S. Manikandan; P. Senthil Kumar; P.R. Yaashikaa; M. Oviyapriya; Gayathri Rangasamy (Fuel, 2023)

MXene-interdigitated Holey-graphene oxide nanocomposite for simultaneous detection of antibiotic and anticancer drugs with ultra-high sensitivity - Ramadhass Keerthika Devi; Muthusankar Ganesan; Tse-Wei Chen; Shen-Ming Chen; Arshad Mehmood Abbasi; M. Ajmal Ali; Mohamed S. Elshikh; Jaysan Yu; Hsin-Yu Chuang; Bolin Xu; Sai Kishore Ravi (Chemical Engineering Journal, 2023)

New Record of Champsodon Atridorsalis Ochiai & Nakamura, 1964 from the South Eastern Arabian Sea - Rekha Devi Chakraborty; G. Maheswarudu; P. T. Jinesh; N Ragesh; L Sreesanth; Josileen Jose; Pillai S Lakshmi; A P Dineshbabu; Rajendra Naik; T B Retheesh (Thalassas: An International Journal of Marine Sciences, 2023)

Intraspecific inflorescence and palynological variations in the morphotypes of Amorphophallus paeoniifolius - Shirly Raichal Anil; A. Asha Devi; K. I. Asha; S. Suhara Beevy; E. A. Siril (Genetic Resources and Crop Evolution, 2023)

Lithium-ion cells for space applications: Aspects of durability - M. Dev Anand; Reshmi Sasidharakurup; T.D Mercy; Thomson.M. Jacob; S. Athula Devi (Advances in Space Research, 2023)

Effect of algal metabolites in the inhibition of angiogenic channels for breast tumour - Risav Banerjee; Rajdeep Das; Amrutha VM; Asha Devi S; Sudhakaran R (Aquaculture International, 2023)

Reproductive traits, dynamics of oogenesis and embryonic developments in the deep-sea shrimp Plesionika semilaevis from the southeastern Arabian sea - S. Sreelakshmy; Rekha Devi Chakraborty (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Synthesis and evaluation of metal-impregnated carbon cloth supplementation to improve anaerobic digestion performance from municipal sludge - Vikas Kumar; Parmila Devi; Abhishek Patil; Juan Camilo Santana; Jake S. Bobowski; Steven J. Hallam; Cigdem Eskicioglu (Chemical Engineering Journal, 2023)

An optimal deep learning model for recognition of hidden hazardous weapons in terahertz and millimeter wave images - J. Jayachitra; Suganya Devi K; S. V. Manisekaran; Satish Kumar Satti (Earth Science Informatics, 2023)

Influence of age, diurnal cycle, and plant and non-plant surfaces on oviposition by Spodoptera litura (Fabricius)(Lepidoptera: Noctuidae) - S. P. Yadav Deen; Anupam Varshney Sharma; Priya Singh; Satish Ganta; P. R. Ragesh; Smriti Sharma; Tarkeshwar; Kapinder; Jyotsna Singh; Mayanglambam Rojina Devi; Sanjiv Mullick (International Journal of Tropical Insect Science, 2023)

Sedimentary seagrass carbon stock and sources of organic carbon across contrasting seagrass meadows in Indonesia - Yusmiana P. Rahayu; Mariska A. Kusumaningtyas; August Daulat; Agustin Rustam; Devi D. Suryono; Hadiwijaya L. Salim; Restu N. A. Ati; Nasir Sudirman; Terry L. Kepel; Andreas A. Hutahaean; Novi S. Adi (Environmental Science and Pollution Research, 2023)
Seagrass meadows are an important component of coastal ecosystems globally, and they capture and store organic carbon in living biomass and sediments. Geographical estimates of blue carbon in seagrass habitats are regionally biased, with limited information from the Indo-Pacific region, including Indonesia. Seagrass extent in Indonesia is declining rapidly, and it has been suggested that marine protected areas (MPAs) are an important instrument to support protection of seagrass ecosystems and their services. Thus, this study is aimed at quantifying and comparing sedimentary carbon stocks and sources of organic carbon from seagrass meadows located in undisturbed areas outside MPA, disturbed areas outside MPA, and within MPA in three small islands in Indonesia. The sediment carbon stocks from this study ranged from 19.81 to 117.49 Mg C ha −1 , with the highest stock measured inside MPA (77.15 ± 1.38 Mg C ha −1 ), followed by undisturbed outside MPA (36.08 Mg C ha −1 ), and the lowest stock at disturbed outside MPA (21.86 ± 0.31 Mg C ha −1 ). The predominant source of organic carbon in disturbed meadows was from coastal POM (particulate organic matter, ~ 36%), while in MPA and undisturbed sites, the main source was from seagrass, with ~ 38% and ~ 60% contributions, respectively. The results of this study add more data and information on seagrass blue carbon potential from three different islands with different degrees of disturbance in Indonesia.

Evaluation of in vitro glucose metabolism potential of sterols and essential oil extracts from Erythroxylum monogynum Roxb. using cell lines and enzyme inhibition models - J. Achyutha Devi; G. Bindu; S. Ravi Kiran (South African Journal of Botany, 2023)

Identifying optimum residue levels for stable crop and water productivity and carbon sequestration under a conservation agriculture based rice-wheat system - Ram Swaroop Bana; Shanti Devi Bamboriya; Vipin Kumar; Samarth Godara; Donald S. Gaydon; Alison M. Laing; Rajkumar Dhakar; Y.S. Shivay; Vijay Singh Meena; Deepak Singh (Soil and Tillage Research, 2023)

Selenium nanomaterial is a promising nanotechnology for biomedical and environmental remediation: A detailed review - M. Sindhu Devi; S. Srinivasan; A. Muthuvel (Biocatalysis and Agricultural Biotechnology, 2023)

Functionalization of Pristine Coconut Husk (Cocos nucifera) with Sodium Vinyl Sulfonate for Removal of Toxic Hg2+ Ions from Wastewater - Kavita Devi; Anamika Ramchaik; Ghanshyam S. Chauhan; Sunita Ranote; Sandeep Chauhan; Kiran Kumar (Water, Air, & Soil Pollution, 2023)

Which side are you on? Spider web positioning affects prey capture more than body colour - Fabian C. Salgado-Roa; Devi Stuart-Fox; Edwin Castañeda; Maira S. Tique Obando; Iliana Medina (Evolutionary Ecology, 2023)
Colour has been hypothesized to play a crucial role in prey capture for sit-and-wait predators that rely on visual cues to deceive their prey. Prey capture success has been directly linked to colouration in spiders; however, evidence so far focuses mostly on dorsal colouration, excluding ventral patterns that are visible to prey and may be relevant for prey attraction. Here, we explored whether the dorsal and ventral colouration of a colour polymorphic spider is associated with light environment and prey capture success. We quantified the number of prey captured across three dorsal (black, white, and yellow) and two ventral (black and a mosaic yellow/orange pattern) morphs of Gasteracantha cancriformis , considering light intensity on dorsal and ventral sides. We found that spiders capture more prey in low light environments, and that individuals often expose their dorsal colouration towards low light levels. We did not find significant differences in prey capture rate between morphs dorsally or ventrally. These results indicate that how and where spiders position their web can be more important for prey capture than colouration. Alternative hypotheses such as aposematism, camouflage and thermoregulation deserve more attention in future studies that aim to understand the role of colouration in spiders and the factors causing spider colour polymorphisms.

Monitoring early-season agricultural drought using temporal Sentinel-1 SAR-based combined drought index - T. Dilip; Mamta Kumari; C. S. Murthy; T. L. Neelima; Abhishek Chakraborty; M. Uma Devi (Environmental Monitoring and Assessment, 2023)

Feeding ecology of the pandalid shrimp, Plesionika semilaevis (Spence Bate 1888) in South Eastern Arabian Sea - Sreelakshmy S.; Rekha Devi Chakraborty; Sreesanth L. (Regional Studies in Marine Science, 2023)

Comparative assessment of soil microbial community in crude oil contaminated sites - Guneshwari Yerulker; Priya Patel; Ayushi Chafale; Visha Rathod; Sandeep Das; Piyush Pandey; Noor Afshan Khan; Arundhuti Devi; Nasreen S. Munshi; Rita Dhodapkar; Atya Kapley (Environmental Pollution, 2023)

Association of DAZL polymorphisms and DAZ deletion with male infertility: a systematic review and meta-analysis - Puja Devi Nongthombam; Suttur S. Malini (Genes & Genomics, 2023)

Extraction of essential oil from Assam lemon peels and its incorporation in chitosan based coating for maintaining grape quality - Jishuraj Chetia; Pragyan Adhikary; Lourembam Monika Devi; Laxmikant S. Badwaik (Sustainable Chemistry and Pharmacy, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Microstructural and Cantabro loss studies on self-healing concrete with crushed stone sand, Bacillus subtilis bacteria and calcium lactate - C. Venkata Siva Rama Prasad; T. V. S. Vara Lakshmi; G. Sree Lakshmi Devi (Innovative Infrastructure Solutions, 2023)

Hexagonal nanosheets of pyrrochlore-type lanthanum stannate for sensitive detection of chlorinated pesticide in food and environmental samples - Ramadhass Keerthika Devi; Muthusankar Ganesan; Tse-Wei Chen; Shen-Ming Chen; Rabab Ahmed Rasheed; Wedad A. Al-onazi; Mohamed S Elshikh; Xiaoheng Liu; Jaysan Yu (Food Chemistry, 2023)

Efficacy and physical modes of EBI and strobilurin fungicides in managing French bean rust (Uromyces appendiculatus) - Gurvinder Singh; Banita Devi; S. K. Gupta; Pramod Prasad (Indian Phytopathology, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System - Snigdha S. Majhi; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Janmejay Parhi; Soibam Ngasotter; Gusheinzed Waikhom; Dharmendra Kumar Meena; Ayam Gangarani Devi; Sudhanshu S. Mahanand; K. A. Martin Xavier; Arun Bhai Patel (Fishes, 2023)
Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimaculatus. Advanced fry (1.21 ± 0.08 g) was reared in a zero-water exchange biofloc system for 90 days at stocking densities of 0.5 g/L(T1), 1.0 g/L(T2), 1.5 g/L(T3) and 2.0 g/L(T4). The observed water quality indicates a reduction in DO and pH in T4, while the total ammonia nitrogen and nitrite levels remained low in T1. Among the groups, highest weight gain was noticed in the lowest stocking density (0.5 g/L) (p

Genetic resources of sticky rice in India: status and prospects - Raj K. Gautam; Sapna Langyan; S. Vimla Devi; Rakesh Singh; D. P. Semwal; Sharik Ali; G. S. Mangat; Sutapa Sarkar; Torit Baran Bagchi; Somnath Roy; P. Senguttuvel; S. Bhuvaneswari; et al. (Genetic Resources and Crop Evolution, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Evaluation of the Anti-Inflammatory Activity of Kokilaksham kashayam on Lipopolysaccharide Stimulated RAW 264.7 Macrophages - Teena Merlin; M. B. Bashi; S. J. Rahitha Devi; B. Prakash Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Trends in breast and prostate cancer screening and diagnostic procedures during the COVID-19 pandemic in central Massachusetts - Mara M. Epstein; Devi Sundaresan; Meagan Fair; Hassan Fouayzi; Erica T. Warner; Lawrence D. Garber; Jerry H. Gurwitz; Terry S. Field (Cancer Causes & Control, 2022)

Bacterial diversity of a floating vegetation (Phumdi) of Loktak Lake and its extracellular enzymes and bacterial antagonistic property - Jusna Nandeibam; Y Randhir Babu Singh; K Chandradev Sharma; Kh. Ranjana Devi; Pulok Kumar Mukherjee; S Indira Devi (Archives of Microbiology, 2022)

Fungal disease suppression and growth promotion potential of endophytic bacteria from ethnomedicinal plants - Rakhi Khunjamayum; K. Tamreihao; Roshan Singh Asem; Yurembam Rojiv Singh; Amanda Nongthombam; Khuraijam Mrinalini Devi; Thoudam Pooja Chanu; Laishram Jaya Devi; Saikat Mukherjee; Debananda S. Ningthoujam (Archives of Microbiology, 2022)

Toxicity Assessment of Fluoride-Contaminated Soil and Wastewater in Solanum tuberosum - Gitika Devi; Anamika Kushwaha; Lalit Goswami; Sutapa Chakrabarty; Hardeep Kaur; Sandip S. Sathe; Kanchan Bahukhandi; Uday Bhan; Hari Prasad Sarma (Water, Air, & Soil Pollution, 2022)

Virgin Coconut Oil (VCO) Ameliorates High Fat Diet (HFD)-Induced Obesity, Dyslipidemia and Bestows Cardiovascular Protection in Rats - Shilpa S. Shetty; P. G. Roopashree; S. V. Ramesh; Ajeet Singh; M. Arivalagan; M. R. Manikantan; Ullal Harshini Devi; K. P. Sharmila; K. B. Hebbar; N. Suchetha Kumari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Upper layer characteristics of the South Eastern Arabian Sea associated with an unusual low saline pool during fag end of southwest monsoon - S Vishnu Narayanan Nampoothiri; Muhammad Shafeeque; V S Arun; B R Smitha; Kusum Komal Karati; K Rasheed; C R Asha Devi; Hashim Manjebrayakath (Journal of Earth System Science, 2022)

Mercury transportation dynamics in the Ganga Alluvial Plain, India: rainwater–groundwater–river water interaction study from hotspot region - V. Devi; M. M. Atique; A. Raju; G. Upreti; D. K. Jigyasu; J. K. Yadav; S. Singh; R. Kar; M. Singh (International Journal of Environmental Science and Technology, 2022)

Evaluation of brinjal germplasm against root-knot nematode, Meloidogyne incognita - Bharat H. Gawade; Shikha Chaturvedi; Zakaullah Khan; Chithra Devi Pandey; K. K. Gangopadhyay; S. C. Dubey; V. Celia Chalam (Indian Phytopathology, 2022)

Non-thermal plasmas for disease control and abiotic stress management in plants - Susmita C.; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Eric Lichtfouse; Bhojaraj Naik; Ramya P.; Kalyani Kumari; Sanjay Kumar (Environmental Chemistry Letters, 2022)

Apomixis: A Foresight from Genetic Mechanisms to Molecular Perspectives - C. Susmita; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Dinesh K. Agarwal (The Botanical Review, 2022)

Achieving higher production from low inputs using synergistic crop interactions under maize-based polyculture systems - S. D. Bamboriya; Ram Swaroop Bana; Bhola Ram Kuri; Vipin Kumar; Sumitra Devi Bamboriya; Rajendra Prasad Meena (Environmental Sustainability, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Simultaneous estimation of site response and source parameters of reservoir-triggered earthquakes using data from the borehole seismic network in the Koyna–Warna seismic zone, Maharashtra, India - Prantik Mandal; H. V. S. Satayanarayana; D. Shashidhar; Arti Devi; D. Srinagesh (Natural Hazards, 2022)

Designing of peptide aptamer targeting the receptor-binding domain of spike protein of SARS-CoV-2: an in silico study - Arpita Devi; Nyshadham S. N. Chaitanya (Molecular Diversity, 2022)

Unmanned Aerial Vehicle-Based Multispectral Remote Sensing for Commercially Important Aromatic Crops in India for Its Efficient Monitoring and Management - Sonam Bahuguna; Shubham Anchal; Deepak Guleria; Mamta Devi; Meenakshi; Devshree Kumar; Rakesh Kumar; P. V. S. Murthy; Amit Kumar (Journal of the Indian Society of Remote Sensing, 2022)

Pathophysiological basis in the management of myasthenia gravis: a mini review - Aiswarya Binu; Sarath S. Kumar; Uma Devi Padma; Krishnadas Madhu (Inflammopharmacology, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Temperature-duration-frequency analysis over Delhi and Bengaluru city in India - Rani Devi; K. C. Gouda; S. Lenka (Theoretical and Applied Climatology, 2022)

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Biodegradation of low-density polyethylene and polypropylene by microbes isolated from Vaigai River, Madurai, India - K. Nanthini Devi; P. Raju; P. Santhanam; S. Dinesh Kumar; N. Krishnaveni; J. Roopavathy; P. Perumal (Archives of Microbiology, 2021)

Mycobacterium tuberculosis strain lineage in mixed tribal population across India and Andaman Nicobar Island - Azger Dusthackeer; Ashok Kumar; Sucharitha Kannappan Mohanvel; B. Mahizhaveni; S. Shivakumar; S. Raghavi; S. Azhagendran; S. Vetrivel; Vikas Gangadhar Rao; Rajiv Yadav; Vijayachari Paluru; Anil Jacob Purthy; et al. (World Journal of Microbiology and Biotechnology, 2021)

Gibberellic acids promote growth and exopolysaccharide production in Tetraselmis suecica under reciprocal nitrogen concentration: an assessment on antioxidant properties and nutrient removal efficacy of immobilized iron-magnetic nanoparticles - A. Prathipa; G. Manigandan; S. Dinesh Kumar; P. Santhanam; P. Perumal; N. Krishnaveni; K. Nanthini Devi; S. Vijayalakshmi (Archives of Microbiology, 2021)

Trends of winter precipitation extremes over Northwest Himalaya - N. Narasimha Rao; Usha Devi; M. S. Shekhar; G. P. Singh (Hydrological Sciences Journal, 2021)

Molecular Characterization on the Morphotypes of Amphiprion clarkii (Bennett, 1830) from Indian Waters with Biogeographic Notes - Vyshnavi Devi S; Salitha S; Sheena Jose; Purushothaman Paramasivam; Jasmine Anand; Ajith Kumar T. T.; Kuldeep Kumar Lal (Thalassas: An International Journal of Marine Sciences, 2021)

A Review on SARS-CoV-2-Induced Neuroinflammation, Neurodevelopmental Complications, and Recent Updates on the Vaccine Development - Medha Karnik; Narasimha M. Beeraka; Chinnappa A. Uthaiah; Suma M. Nataraj; Anjali Devi S. Bettadapura; Gjumrakch Aliev; SubbaRao V. Madhunapantula (Molecular Neurobiology, 2021)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Folic Acid as a Bimodal Optical Probe for the Detection of TNT - N. S. Vijila; M. Athira; S. Madanan Anju; A. O. Aswathy; J. Jayakrishna; Mrudula Sreekumar; J. S. Anjali Devi; B. Anjitha; Sony George (Journal of Fluorescence, 2021)

Impact of stochastic perturbation on the persistence and extinction risk of a multi-delayed prey–predator system in non-autonomous environment - N. S. N. V. K. Vyshnavi Devi; Debaldev Jana (Modeling Earth Systems and Environment, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

QTLs in salt rice variety CSR10 reveals salinity tolerance at reproductive stage - Preeti Pundir; Ashwanthi Devi; S. L. Krishnamurthy; Parbodh Chander Sharma; N. M. Vinaykumar (Acta Physiologiae Plantarum, 2021)

Correction of mesoscale model daily precipitation data over Northwestern Himalaya - Usha Devi; M. S. Shekhar; G. P. Singh (Theoretical and Applied Climatology, 2021)

Cryopreservation of shoot tips of Gentiana kurroo Royle – a critically endangered medicinal plant of India - Neelam Sharma; R. Gowthami; S. Vimala Devi; Era Vaidya Malhotra; Ruchira Pandey; Anuradha Agrawal (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Investigation of Heavy Atom Effect on Fluorescence of Carbon Dots: NCDs and S,N-CDs - A. O. Aswathy; S. Madanan Anju; J. Jayakrishna; N. S. Vijila; J. S. Anjali Devi; B. Anjitha; Sony George (Journal of Fluorescence, 2020)

Evaluation of anti-inflammatory effects of polyherbal decoction, balaguluchyadi kashayam - S. J. Rahitha Devi; B. Prakash Kumar; M. B. Bashi; J. U. Chinchu; Teena Merlin (Advances in Traditional Medicine, 2020)

Efficacy of new generation fungicides against French bean rust caused by Uromyces appendiculatus - Banita Devi; S. K. Gupta; Gurvinder Singh; Pramod Prasad (Phytoparasitica, 2020)

Latitudinal decline in stand biomass and productivity at the elevational treeline in the Ural mountains despite a common thermal growth limit - Frank Hagedorn; Melissa A. Dawes; Maxim O. Bubnov; Nadezhda M. Devi; Andrey A. Grigoriev; Valeriy S. Mazepa; Zufar Y. Nagimov; Stepan G. Shiyatov; Pavel A. Moiseev (Journal of Biogeography, 2020)
Aim To quantify tree biomass and stand productivity of treeline ecotones and identify driving factors. Location treeline ecotones of seven regions from the South to Polar Urals, spanning a latitudinal gradient of 1,500 km. Taxa Picea obovata , Betula pubescens , Larix sibirica. Methods Stand biomass and productivity were estimated across 18 elevational transects from the tree species line to the closed forest line based on allometric measurements of 326 trees (including roots for 53 trees), stand structure assessments and demographic patterns of 20,600 trees. Stand growth data were linked to (a) temperatures monitored in situ for five years in the South and Polar Urals, (b) climate variables extrapolated from nearby climate stations and (c) measures of nutrient availability in soils and tree foliage. Results treeline position along the latitudinal gradient occurred at a similar mean growing season temperature. Despite the common cold limitation of tree distribution along the Ural mountain range, stand biomass and productivity within the treeline ecotone decreased by a factor of three and five from the South to the Polar Urals, mainly due to a declining stand density. Among climatic variables, growing season length decreased by 20% and winter temperatures declined by 4°C towards the Polar Urals, whereas growing degree days > 5°C remained similar, averaging 554 ± 9°C. Soil development was poorer in the Polar than in the South Urals, and plant‐available N and P in the soil were 20 and 30 times lower, respectively, probably due to lower winter temperatures. Main conclusions Our results suggest that once the thermal limitation for tree growth is relieved, soil fertility—restricted by permafrost and low soil temperatures during winter—plays a key and yet underexplored role for stand productivity in treeline ecotones. The observed latitudinal decline in stand productivity is important for above‐ and belowground diversity and functioning.

Statistical Method of Forecasting of Seasonal Precipitation over the Northwest Himalayas: North Atlantic Oscillation as Precursor - Usha Devi; M. S. Shekhar; G. P. Singh; S. K. Dash (Pure and Applied Geophysics, 2020)

Novel formulations of Bacillus thuringiensis var. kurstaki: an eco-friendly approach for management of lepidopteran pests - P. S. Vimala Devi; P. Duraimurugan; K. S. V. Poorna Chandrika; V. Vineela; P. P. Hari (World Journal of Microbiology and Biotechnology, 2020)

Efficacy of mating disruption compared with chemical insecticides for controlling Tuta absoluta (Lepidoptera: Gelechiidae) in Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Joby Jacob; Omar Al-Saeed (Applied Entomology and Zoology, 2020)

An effective method for extraction of high purity phycocyanins (C-PC and A-PC) from dry biomass of Arthrospira maxima - A. Chandralekha Devi; Hrishikesh A. Tavanandi; K. Govindaraju; K. S. M. S. Raghavarao (Journal of Applied Phycology, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Abiotic Elicitors Influence Antioxidative Enzyme Activities and Shelf Life of Carrot During Storage Under Refrigerated Conditions - Jomika Devi; Surekha Bhatia; M. S. Alam (Journal of Plant Growth Regulation, 2019)

Strong motion generation area modelling of the 2008 Iwate earthquake, Japan using modified semi-empirical technique - Sandeep; A Joshi; Sonia Devi; Parveen Kumar; S K Sah; Sohan Lal; Kamal (Journal of Earth System Science, 2019)

Modeling of 2011 IndoNepal Earthquake and Scenario Earthquakes in the Kumaon Region and Comparative Attenuation Study Using PGA Distribution with the Garhwal Region - Sandeep; A. Joshi; S. K. Sah; Parveen Kumar; Sohan Lal; Sonia Devi; Monika (Pure and Applied Geophysics, 2019)

Transverse Tectonics Structures in the Garhwal Himalaya Corridor Inferred from 3D Inversion of Magnetotelluric Profile Data - Anita Devi; Mohammad Israil; Pravin K. Gupta; S. K. Varshney; Naser Meqbel (Pure and Applied Geophysics, 2019)

New Records of Two Brachyuran Crabs (Crustacea: Decapoda), Naxioides robillardi (Miers, 1882) (Epialtidae) and Lupocyclus tugelae Barnard, 1950 (Portunidae) from India - Suvarna S. Devi; Appukuttannair Biju Kumar; Peter K. L. Ng (Thalassas: An International Journal of Marine Sciences, 2019)

PHD-2 activation: a novel strategy to control HIF-1α and mitochondrial stress to modulate mammary gland pathophysiology in ER+ subtype - Uma Devi; Manjari Singh; Subhadeep Roy; Avinash C. Tripathi; Pushpraj S. Gupta; Shailendra K. Saraf; Md. Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Orange-fleshed cucumber (Cucumis sativus var. sativus L.) germplasm from North-East India: agro-morphological, biochemical and evolutionary studies - Pragya Ranjan; Anjula Pandey; A. D. Munshi; Rakesh Bhardwaj; K. K. Gangopadhyay; Pavan Kumar Malav; Chithra Devi Pandey; K. Pradheep; B. S. Tomar; Ashok Kumar (Genetic Resources and Crop Evolution, 2019)

Methodological application of quantile mapping to generate precipitation data over Northwest Himalaya - Usha Devi; Manorama S. Shekhar; Gyan P. Singh; Nalamasu N. Rao; Uma S. Bhatt (International Journal of Climatology, 2019)
Continuous high quality data are critical for weather and climate investigations. Numerous data gaps exist particularly over mountainous regions which limits the ability to construct climatologies and perform trend analysis. This study addresses the issue of sparse precipitation data over Northwest Himalaya (NWH) and fills data voids by applying the quantile mapping (QM) method. QM is applied to observed winter precipitation for a period of 25 years (1991–1992 to 2015–2016) to construct a continuous reliable data set. The first 20 years (1991–1992 to 2010–2011) are used for training and the remaining 5 years (2011–2012 to 2015–2016) are used for validation. In total, 10 stations are available for this study and each one is considered serially as a reference to generate daily precipitation values at the other stations. The mean precipitation of NWH region is constructed by considering the mean of all the stations. Standard statistical measures like root mean square errors, standard deviation, skill score and its decompositions are applied to evaluate the generated datasets. Based on statistical analysis, the Kanzalwan station, located in Great Himalaya range, is one of the best performing reference stations for generating precipitation values over NWH. The statistical measures of this station show the highest skill scores, lowest root mean square error and lowest standard mean errors for all winter months except January. This study provides a successful application of QM to generate precipitation data for climate analysis over the complex terrain of the Himalaya region.

Genetic Status and Endosymbionts Diversity of Bemisia tabaci (Gennadius) on Hosts Belonging to Family Malvaceae in India - T R Hashmi; S R Devi; A Ahmad; N M Meshram; R Prasad (Neotropical Entomology, 2019)

Frequent introgression of European cauliflowers in the present day cultivated Indian cauliflowers and role of Indian genotypes in the evolution of tropical cauliflower - S. S. Dey; R. Bhatia; Kanika Sharma; Ila Bhardwaj; Chithra Devi Pandey; Chander Parkash; Raj Kumar (Euphytica, 2019)

Baseline susceptibility and assessment of resistance risk to flubendiamide and chlorantraniliprole in Tuta absoluta (Lepidoptera: Gelechiidae) populations from Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Dawood G. Awadh; Binson M. Thomas (Applied Entomology and Zoology, 2019)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Variability of Diurnal Temperature Range During Winter Over Western Himalaya: Range- and Altitude-Wise Study - M. S. Shekhar; Usha Devi; S. K. Dash; G. P. Singh; Amreek Singh (Pure and Applied Geophysics, 2018)

Effect of early natal supplementation of paracetamol on attenuation of exotoxin/endotoxin induced pyrexia and precipitation of autistic like features in albino rats - Abdulaziz S. Saeedan; Indu Singh; Mohd. Nazam Ansari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Swetlana Gautam; Rajnish K. Yadav; Gaurav Kaithwas (Inflammopharmacology, 2018)

Simultaneous quantitative monitoring of four indicator contaminants of emerging concern (CEC) in different water sources of Central India using SPE/LC-(ESI)MS-MS - Roshan Appa; V. A. Mhaisalkar; Amit Bafana; S. Saravana Devi; Kannan Krishnamurthi; Tapan Chakrabarti; Pravin K. Naoghare (Environmental Monitoring and Assessment, 2018)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Bioactivity of Marine Streptomyces sp. VITJS4: Interactions of Cytotoxic Phthalate Derivatives with Human Topoisomerase II α: An In Silico Molecular Docking Analysis - S. Jemimah Naine; C. Subathra Devi; V. Mohanasrinivasan; C. George Priya Doss (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Phenazine‐1‐carboxylic acid and soil moisture influence biofilm development and turnover of rhizobacterial biomass on wheat root surfaces - Melissa K. LeTourneau; Matthew J. Marshall; John B. Cliff; Robert F. Bonsall; Alice C. Dohnalkova; Dmitri V. Mavrodi; S. Indira Devi; Olga V. Mavrodi; James B. Harsh; David M. Weller; Linda S. Thomashow (Environmental Microbiology, 2018)
Summary Phenazine‐1‐carboxylic acid (PCA) is produced by rhizobacteria in dryland but not in irrigated wheat fields of the Pacific Northwest, USA. PCA promotes biofilm development in bacterial cultures and bacterial colonization of wheat rhizospheres. However, its impact upon biofilm development has not been demonstrated in the rhizosphere, where biofilms influence terrestrial carbon and nitrogen cycles with ramifications for crop and soil health. Furthermore, the relationships between soil moisture and the rates of PCA biosynthesis and degradation have not been established. In this study, expression of PCA biosynthesis genes was upregulated relative to background transcription, and persistence of PCA was slightly decreased in dryland relative to irrigated wheat rhizospheres. Biofilms in dryland rhizospheres inoculated with the PCA‐producing (PCA + ) strain Pseudomonas synxantha 2‐79RN 10 were more robust than those in rhizospheres inoculated with an isogenic PCA‐deficient (PCA ‐ ) mutant strain. This trend was reversed in irrigated rhizospheres. In dryland PCA + rhizospheres, the turnover of 15 N‐labelled rhizobacterial biomass was slower than in the PCA ‐ and irrigated PCA + treatments, and incorporation of bacterial 15 N into root cell walls was observed in multiple treatments. These results indicate that PCA promotes biofilm development in dryland rhizospheres, and likely influences crop nutrition and soil health in dryland wheat fields.

Synthesis, Photoluminescence Behavior of Green Light Emitting Tb(III) Complexes and Mechanistic Investigation of Energy Transfer Process - Manju Bala; Satish Kumar; Rekha Devi; Avni Khatkar; V. B. Taxak; Priti Boora; S. P. Khatkar (Journal of Fluorescence, 2018)

Influence of sea grapes (Caulerpa racemosa) supplementation on physical, functional, and anti-oxidant properties of semi-sweet biscuits - Anuj Kumar; Elavarasan Krishnamoorthy; Hanjabam Mandakini Devi; Devananda Uchoi; C. S. Tejpal; George Ninan; A. A. Zynudheen (Journal of Applied Phycology, 2018)

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Purification and Characterization of Extracellular Lipase from Serratia marcescens VITSD2 - V. Mohanasrinivasan; C. Subathra Devi; D. Jayasmita; E. Selvarajan; S. Jemimah Naine (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Analytical Techniques Used to Detect DNA Binding Modes of Ruthenium(II) Complexes with Extended Phenanthroline Ring - C. Shobha Devi; B. Thulasiram; S. Satyanarayana; Penumaka Nagababu (Journal of Fluorescence, 2017)

Relative Study of Luminescent Properties with Judd-Ofelt Characterization in Trivalent Europium Complexes Comprising ethyl-(4-fluorobenzoyl) Acetate - Rekha Devi; Sangeeta Chahar; S. P. Khatkar; V. B. Taxak; Priti Boora (Journal of Fluorescence, 2017)

Effects of Water pH on Life History Parameters of a New Bosminid Cladocera: Bosmina (Bosmina) Tripurae (Korinek, Saha and Bhattachaya, 1999) in Laboratory Condition - Himadri Saha; K. S. Wisdom; Asem Lembika Devi; Da-u-ruhi Pde; Sukham Tuni Devi; Makamguang Kamei; Anamika Biswas; Ratan K. Saha; Prasenjit Pal (Bulletin of Environmental Contamination and Toxicology, 2017)

A Novel Approach of Despeckling SAR Images Using Nonlocal Means Filtering - Devi Devapal; S. S. Kumar; Christy Jojy (Journal of the Indian Society of Remote Sensing, 2017)

Correlation Between Molecular Modelling and Spectroscopic Techniques in Investigation With DNA Binding Interaction of Ruthenium(II) Complexes - B. Thulasiram; C. Shobha devi; Yata Praveen Kumar; Rajeshwar Rao Aerva; S. Satyanarayana; Penumaka Nagababu (Journal of Fluorescence, 2017)

Differential behaviour of a Lesser Himalayan watershed in extreme rainfall regimes - Pankaj Chauhan; Nilendu Singh; Devi Datt Chauniyal; Rajeev S Ahluwalia; Mohit Singhal (Journal of Earth System Science, 2017)

Treeline advances and associated shifts in the ground vegetation alter fine root dynamics and mycelia production in the South and Polar Urals - Emily F. Solly; Ika Djukic; Pavel A. Moiseev; Nelly I. Andreyashkina; Nadezhda M. Devi; Hans Göransson; Valeriy S. Mazepa; Stepan G. Shiyatov; Marina R. Trubina; Fritz H. Schweingruber; Martin Wilmking; Frank Hagedorn (Oecologia, 2017)

Developing a biosorbent from Aegle Marmelos leaves for removal of methylene blue from water - S. Baruah; A. Devi; K. G. Bhattacharyya; A. Sarma (International Journal of Environmental Science and Technology, 2017)

Effect of PEG and water-soluble chitosan coating on moxifloxacin-loaded PLGA long-circulating nanoparticles - Sanaul Mustafa; V. Kusum Devi; Roopa S Pai (Drug Delivery and Translational Research, 2017)

Foraminifera of Lakshadweep Archipelago, Arabian Sea - Subhadra Devi Gadi; P. Vidya; M. S. Mustak; K. P. Rajashekhar (Proceedings of the Zoological Society, 2016)

Studies on Photocleavage, DNA Binding, Cytotoxicity, and Docking Studies of Ruthenium(II) Mixed Ligand Complexes - Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; N. Deepika; V. Ravi Kumar; P. Venkat Reddy; K Nagasuryaprasad; Surya S. Singh; Penumaka Nagababu; S. Satyanarayana (Journal of Fluorescence, 2016)

α-Chymotrypsin regulates free fatty acids and UCHL-1 to ameliorate N-methyl nitrosourea induced mammary gland carcinoma in albino wistar rats - Asha Rani; Subhadeep Roy; Manjari Singh; Uma Devi; Rajnish K. Yadav; Swetlana Gautam; Jitendra K. Rawat; Mohd. Nazam Ansari; Abdulaziz S. Saeedan; Anand Prakash; Gaurav Kaithwas (Inflammopharmacology, 2016)

Redefining the role of peripheral LPS as a neuroinflammatory agent and evaluating the role of hydrogen sulphide through metformin intervention - Virendra Tiwari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Rajnish K. Yadav; Subhadeep Roy; Swetlana Gautam; Shubhini A. Saraf; Vikas Kumar; Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Inflammopharmacology, 2016)

Catalase and ascorbate peroxidase—representative H2O2-detoxifying heme enzymes in plants - Naser A. Anjum; Pallavi Sharma; Sarvajeet S. Gill; Mirza Hasanuzzaman; Ekhlaque A. Khan; Kiran Kachhap; Amal A. Mohamed; Palaniswamy Thangavel; Gurumayum Devmanjuri Devi; Palanisamy Vasudhevan; Adriano Sofo; Nafees A. Khan; et al. (Environmental Science and Pollution Research, 2016)

Copper transporters and chaperones: Their function on angiogenesis and cellular signalling - S R Bharathi Devi; Aloysius Dhivya M; K N Sulochana (Journal of Biosciences, 2016)

Identification of Potential Habitat Patches for Connectivity Using Weighted Linear Combination (WLC) and Integral Index of Connectivity (IIC) at East Godavari District, Andhra Pradesh, India - Shanthala Devi B. S; M. S. R Murthy; Debnath Bijan; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2016)

Production, Purification and Stability Studies on Nattokinase: A Therapeutic Protein Extracted from Mutant Pseudomonas aeruginosa CMSS Isolated from Bovine Milk - C. Subathra Devi; V. Mohanasrinivasan; Pragya Sharma; Daria Das; B. Vaishnavi; S. Jemimah Naine (International Journal of Peptide Research and Therapeutics, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Application of Glass Transition in Food Processing - S. Balasubramanian; Apramita Devi; K. K. Singh; S. J. D Bosco; Ashish M. Mohite (Critical Reviews in Food Science and Nutrition, 2016)

Field level evaluation of rice introgression lines for heat tolerance and validation of markers linked to spikelet fertility - V. Vishnu Prasanth; Kumari Ramana Basava; M. Suchandranath Babu; Venkata Tripura V.G.N.; S. J. S. Rama Devi; S. K. Mangrauthia; S. R. Voleti; N. Sarla (Physiology and Molecular Biology of Plants, 2016)

Design and development of oxobenzimidazoles as novel androgen receptor antagonists - R. Elancheran; K. Saravanan; Bhaswati Choudhury; S. Divakar; S. Kabilan; M. Ramanathan; Babulal Das; R. Devi; Jibon Kotoky (Medicinal Chemistry Research, 2016)

Expression and inheritance of chimeric cry2AX1 gene in transgenic cotton plants generated through somatic embryogenesis - A. R. Sakthi; A. Naveenkumar; P. S. Deepikha; N. Balakrishnan; K. K. Kumar; E. Kokila Devi; V. Balasubramani; L. Arul; P. K. Singh; D. Sudhakar; V. Udayasuriyan; P. Balasubramanian (In Vitro Cellular & Developmental Biology - Plant, 2015)

Nucleotide variation and identification of novel blast resistance alleles of Pib by allele mining strategy - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; M. S. Prasad; V. Ravindra Babu (Physiology and Molecular Biology of Plants, 2015)

New insights of superoxide dismutase inhibition of pyrogallol autoxidation - T. Ramasarma; Aparna V. S. Rao; M. Maya Devi; R. V. Omkumar; K. S. Bhagyashree; S. V. Bhat (Molecular and Cellular Biochemistry, 2015)

Prevalence of peste des petits ruminants in goats in North-East India - V. Balamurugan; Sutopa Das; D. S. N. Raju; Indirani Chakravarty; M. Nagalingam; D. Hemadri; G. Govindaraj; N. Ibotombi Singh; Keduzol Ltu; Maitryee Devi; K. Sharma; M. R. Gajendragad; et al. (VirusDisease, 2014)

Studies on Biosynthesis of Antimicrobial Silver Nanoparticles Using Endophytic Fungi Isolated from the Ethno-medicinal Plant Gloriosa superba L. - Lamabam Sophiya Devi; Donald A. Bareh; S. R. Joshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Persistence and risk assessment of spiromesifen on tomato in India: a multilocational study - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Kousik Mandal; Sanjay K. Sahoo; Hemanta Banerjee; Tirthankar Banerjee; Sankhajit Roy; Paresh G. Shah; Hemlatta K. Patel; Anil R. Patel; S. Naseema Beevi; et al. (Environmental Monitoring and Assessment, 2014)

Activity enhancement of carbonic anhydrase in Chlamydomonas sp. for effective CO2 sequestration - Raju R. Yadav; Kannan Krishnamurthi; Ajam Y. Shekh; Sandeep N. Mudliar; Saravana S. Devi; Tapan Chakrabarti (Clean Technologies and Environmental Policy, 2014)

Residual behavior and risk assessment of flubendiamide on tomato at different agro-climatic conditions in India - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Sanjay K. Sahoo; N. S. Parihar; B. N. Sharma; V. D. Kale; R. V. Nakat; A. R. Walunj; Saudamini Mohapatra; A. K. Ahuja; Debi Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Electrical resistivity imaging over natural (in situ) geological samples using physical model studies - Rajesh Rekapalli; Padmavathi Devi P; V. S. Sarma; P. Rajendra Prasad (Arabian Journal of Geosciences, 2014)

Treeline advances along the Urals mountain range – driven by improved winter conditions? - Frank Hagedorn; Stepan G. Shiyatov; Valeriy S. Mazepa; Nadezhda M. Devi; Andrey A. Grigor'ev; Alexandr A. Bartysh; Valeriy V. Fomin; Denis S. Kapralov; Maxim Terent'ev; Harald Bugman; Andreas Rigling; Pavel A. Moiseev (Global Change Biology, 2014)
High‐altitude treelines are temperature‐limited vegetation boundaries, but little quantitative evidence exists about the impact of climate change on treelines in untouched areas of Russia. Here, we estimated how forest‐tundra ecotones have changed during the last century along the Ural mountains. In the South, North, Sub‐Polar, and Polar Urals, we compared 450 historical and recent photographs and determined the ages of 11 100 trees along 16 altitudinal gradients. In these four regions, boundaries of open and closed forests (crown covers above 20% and 40%) expanded upwards by 4 to 8 m in altitude per decade. Results strongly suggest that snow was an important driver for these forest advances: (i) Winter precipitation has increased substantially throughout the Urals (~7 mm decade −1 ), which corresponds to almost a doubling in the Polar Urals, while summer temperatures have only changed slightly (~0.05 °C decade −1 ). (ii) There was a positive correlation between canopy cover, snow height and soil temperatures, suggesting that an increasing canopy cover promotes snow accumulation and, hence, a more favorable microclimate. (iii) Tree age analysis showed that forest expansion mainly began around the year 1900 on concave wind‐sheltered slopes with thick snow covers, while it started in the 1950s and 1970s on slopes with shallower snow covers. (iv) During the 20th century, dominant growth forms of trees have changed from multistemmed trees, resulting from harsh winter conditions, to single‐stemmed trees. While 87%, 31%, and 93% of stems appearing before 1950 were from multistemmed trees in the South, North and Polar Urals, more than 95% of the younger trees had a single stem. Currently, there is a high density of seedlings and saplings in the forest‐tundra ecotone, indicating that forest expansion is ongoing and that alpine tundra vegetation will disappear from most mountains of the South and North Urals where treeline is already close to the highest peaks.

Cadmium and copper toxicity in three marine macroalgae: evaluation of the biochemical responses and DNA damage - M. Yokesh Babu; L. Palanikumar; N. Nagarani; V. Janaki Devi; S. Ramesh Kumar; C. M. Ramakritinan; A. K. Kumaraguru (Environmental Science and Pollution Research, 2014)

A comparative study on mesozooplankton abundance and diversity between a protected and an unprotected coastal area of Andaman Islands - Honey U. K. Pillai; K. V. Jayalakshmy; A. Biju; K. J. Jayalakshmi; V. T. Paulinose; C. B. L. Devi; V. R. Nair; C. Revichandran; N. R. Menon; C. T. Achuthankutty; S. U. Panampunnayil (Environmental Monitoring and Assessment, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Microsporogenesis and pollen formation in Zingiber officinale Roscoe - S. Subbarayudu; B. Shankar Naik; H. Sunitibala Devi; B. S. Bhau; P. Shaik Sha Valli Khan (Plant Systematics and Evolution, 2014)

Use of nanoclay platelets in food packaging materials: technical and cytotoxicity approach - M. Jorda-Beneyto; N. Ortuño; A. Devis; S. Aucejo; M. Puerto; D. Gutiérrez-Praena; J. Houtman; S. Pichardo; S. Maisanaba; A. Jos (Food Additives & Contaminants: Part A, 2014)

Safety and toxicological evaluation of Rhizopora mucronata (a mangrove from Vellar estuary, India): assessment of mutagenicity, genotoxicity and in vivo acute toxicity - N. Suganthy; K. Karthikeyan; G. Archunan; S. Karutha Pandian; K. Pandima Devi (Molecular Biology Reports, 2014)

DNA-binding and cleavage, cytotoxicity properties of Ru(II) complexes with 2-(4′-chloro-phenyl) imidazo[4,5-f][1,10]phenanthroline, ligand and their “light switch” on–off effect - Nazar Mohammed Gabra; Bakheit Mustafa; Yata Praveen Kumar; C. Shobha Devi; M. Shilpa; Kotha Laxma Reddy; S. Satyanarayana (Medicinal Chemistry Research, 2014)

Synthesis, Characterization, DNA Binding Studies, Photocleavage, Cytotoxicity and Docking Studies of Ruthenium(II) Light Switch Complexes - Nazar Mohammed Gabra; Bakheit Mustafa; Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; P. Venkat Reddy; Kotha Laxma Reddy; S. Satyanarayana (Journal of Fluorescence, 2014)

Assessment of coastal dune characteristics using georadar imaging and sedimentological analysis: Odisha and Visakhapatnam, India - K. Devi; M. C. Raicy; Deshraj Trivedi; P. Srinivasan; S. G. N. Murthy; Ronald J. Goble; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Variation in evergreen and deciduous species leaf phenology in Assam, India - Athokpam Florida Devi; S. C. Garkoti (Trees, 2013)

Fungal biodegradation of phthalate plasticizer in situ - S. Pradeep; P. Faseela; M. K. Sarath Josh; S. Balachandran; R. Sudha Devi; Sailas Benjamin (Biodegradation, 2013)

Integrated approach of assessing sedimentary characteristics of onshore sand deposits on the Velankanni coast, Tamil Nadu, India: sheds light on extreme wave event signatures - K. Devi; C. S. Vijaya Lakshmi; M. C. Raicy; P. Srinivasan; S. G. N. Murthy; S. M. Hussain; Ilya Buynevich; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Measurement of personal and integrated exposure to particulate matter and co-pollutant gases - J. Jai Devi; Tarun Gupta; Rajmal Jat; S. N. Tripathi (Environmental Science and Pollution Research, 2013)

Treatment of vegetable oil mill effluent using crab shell chitosan as adsorbent - M. Geetha Devi; Z. S. Shinoon Al-Hashmi; G. Chandra Sekhar (International Journal of Environmental Science and Technology, 2012)

Delay in virus accumulation and low virus transmission from transgenic rice plants expressing Rice tungro spherical virus RNA - Vidhu Verma; Shweta Sharma; S. Vimla Devi; S. Rajasubramaniam; Indranil Dasgupta (Virus Genes, 2012)

Application of a Chimeric Protein Construct having Enterotoxin B and Toxic Shock Syndrome Toxin Domains of S. aureus in Immunodiagnostics - R. Shylaja; Devi Kalyan Kumar Thakasi; H. S. Murali; K. Prakash Narayana Reddy; H. V. Batra (Indian Journal of Microbiology, 2012)

Effect of Sources and Levels of Phosphorus with Zinc on Yield and Quality of Sugarcane - T. Chitkala Devi; M. Bharathalakshmi; M. B. G. S. Kumari; N. V. Naidu (Sugar Tech, 2012)

Effect of pendimethalin and quizalofop on N2-fixing bacteria in relation to availability of nitrogen in a Typic Haplustept soil of West Bengal, India - Amal C. Das; Hemanta Nayek; S. Devi Nongthombam (Environmental Monitoring and Assessment, 2012)

Detection and Characterization of Pediocin PA-1/AcH like Bacteriocin Producing Lactic Acid Bacteria - S. Manjulata Devi; Prakash M. Halami (Current Microbiology, 2011)

Peroxyl-induced oxidative stress in aging erythrocytes of rat - S. Asha Devi; C. S. Shiva Shankar Reddy; M. V. V. Subramanyam (Biogerontology, 2011)

Physicochemical characteristics of paper industry effluents—a case study of South India Paper Mill (SIPM) - Ningombam Linthoingambi Devi; Ishwar Chandra Yadav; Q. I. Shihua; Surendra Singh; S. L. Belagali (Environmental Monitoring and Assessment, 2011)

Application of GIS for Evaluation and Design of Watershed Guidelines - R. S. Bhalla; Neil W. Pelkey; K. V. Devi Prasad (Water Resources Management, 2011)

Screening of Rhizobacteria for Their Plant Growth Promotion Ability and Antagonism Against Damping off and Root Rot Diseases of Broad Bean (Vicia faba L.) - S. Indira Devi; N. C. Talukdar; K. Chandradev Sharma; K. Jeyaram; M. Rohinikumar (Indian Journal of Microbiology, 2011)

Hemoglobin-derived Peptides as Novel Type of Bioactive Signaling Molecules - Ivone Gomes; Camila S. Dale; Kimbie Casten; Miriam A. Geigner; Fabio C. Gozzo; Emer S. Ferro; Andrea S. Heimann; Lakshmi A. Devi (The AAPS Journal, 2010)

Relative efficacy of strobilurin formulations in the control of downy mildew of sunflower - J. Sudisha; S. R. Niranjana; S. L. Sukanya; R. Girijamba; N. Lakshmi Devi; H. Shekar Shetty (Journal of Pest Science, 2010)

Economic analysis of risk of gastrointestinal parasitic infection in cattle in North Eastern States of India - S. Bandyopadhyay; S. Mandal; K. K. Datta; P. Devi; S. De; A. K. Bera; D. Bhattacharya (Tropical Animal Health and Production, 2010)

Geospatial modelling for identification of potential ecological corridors in Orissa - A. Roy; B. S. S. Devi; B. Debnath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

Oxidative stress in erythrocytes: a study on the effect of antioxidant mixtures during intermittent exposures to high altitude - R. Vani; C. S. Shiva Shankar Reddy; S. Asha Devi (International Journal of Biometeorology, 2010)

Acclimatory response to hydrogen peroxide and glutathione under salt-boron stress through their impact on mineral nutrition and antioxidant defense system in pigeonpea (Cajanus cajan L.) - S. Chawla; S. C. Goyal; Rajiv Angrish; C. Rani; V. Arora; K. S. Datta; S. Madaan; S. Devi (Physiology and Molecular Biology of Plants, 2010)

Sarcoptic mange infestation in pigs in a hilly region of Meghalaya - M. Das; R. Laha; P. Devi; R. K. Bordoloi; S. Naskar (Tropical Animal Health and Production, 2010)

Multiplex PCR for identification of parasitic eggs of Oesophagostomum spp. Isolated from sheep and goat - S. Bandyopadhyay; S. Naskar; P. Devi; A. K. Bera; S. De; D. Pan; T. Rana; S. Das; S. Sikdar; D. Bhattacharya (Proceedings of the Zoological Society, 2009)

Oxidative stress and intracellular pH in the young and old erythrocytes of rat - S. Asha Devi; C. S. Shiva Shankar Reddy; M. V. V. Subramanyam (Biogerontology, 2009)

Sex steroid correlates of female-specific colouration, behaviour and reproductive state in Lake Eyre dragon lizards, Ctenophorus maculosus - Tim S. Jessop; Rita Chan; Devi Stuart-Fox (Journal of Comparative Physiology A, 2009)

Age-related responses of the rat cerebral cortex: influence of vitamin E and exercise on the cholinergic system - A. B. Jolitha; M. V. V. Subramanyam; S. Asha Devi (Biogerontology, 2009)

Genotoxicity of sludges, wastewater and effluents from three different industries - K. Krishnamurthi; S. Saravana Devi; J. G. Hengstler; Matthias Hermes; Koel Kumar; Dipanwita Dutta; S. Muhil Vannan; T. S. Subin; R. R. Yadav; T. Chakrabarti (Archives of Toxicology, 2008)

Evaluation of in vitro antimicrobial activity of leaf and stem essential oils of Chloroxylon swietenia DC. - S. Ravi Kiran; P. Sita Devi; K. Janardhan Reddy (World Journal of Microbiology and Biotechnology, 2008)

Characterization of Bacillus thuringiensis Strain DOR4 Toxic to Castor Semilooper Achaea janata: Proteolytic Processing and Binding of Toxins to Receptors - Madhusudhan Budatha; Gargi Meur; P. S. Vimala Devi; P. B. Kirti; Aparna Dutta-Gupta (Current Microbiology, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Serum homocysteine levels in cerebrovascular accidents - Zolianthanga Zongte; L. Shaini; Asis Debbarma; Th Bhimo Singh; S. Bilasini Devi; W. Gyaneshwar Singh (Indian Journal of Clinical Biochemistry, 2008)

Remote sensing and GIS application for land quality assessment for coffee growing areas of Karnataka - G. M. Shalima Devi; K. S. Anil Kumar (Journal of the Indian Society of Remote Sensing, 2008)

In vitro production of azadirachtin from cell suspension cultures of Azadirachta indica - S. Sujanya; B. Poornasri Devi; Isha Sai (Journal of Biosciences, 2008)

Effect of vitamin E on protein bound carbhohydrate complexes in radiation treated oral squamous cell carcinoma patients - S. Chitra; C. S. Shyamala Devi (Indian Journal of Clinical Biochemistry, 2008)

Identification of a high frequency of chromosomal rearrangements in the centromeric regions of prostate cancer patients - V. Balachandar; B. Lakshman Kumar; K. Sasikala; P. Manikantan; R. Sangeetha; S. Mohana Devi (Journal of Zhejiang University-SCIENCE B, 2007)

In Vitro Clonal Propagation and Medium Term Conservation of Brahmi [Bacopa monnieri (L) Wettst] - Neelam Sharma; Richa Satsangi; Ruchira Pandey; S. Vimala Devi (Journal of Plant Biochemistry and Biotechnology, 2007)

Effect ofVitex negundo leaf extract on the free radicals scavengers in complete Freund's adjuvant induced arthritic rats - P Renuka Devi; S Krishna Kumari; C Kokilavani (Indian Journal of Clinical Biochemistry, 2007)

Lipid peroxidation and antioxidant vitamins in urolithasis - J Kato; Alice Abraham Ruram; S Sekharjit Singh; S Bilasini Devi; Th Ibetombi Devi; W Gyaneshwar Singh (Indian Journal of Clinical Biochemistry, 2007)

Formulation and evaluation of ketorolac tromethamine-loaded albumin microspheres for potential intramuscular administration - Sam T. Mathew; S. Gayathri Devi; KV Sandhya; KV Sandhya (AAPS PharmSciTech, 2007)

In Vitro Propagation of a Threatened, Anticarcinogenic Herb, Curculigo orchioides Gaertn - Neelam Sharma; S. Vimala Devi; Ruchira Pandey (Journal of Plant Biochemistry and Biotechnology, 2007)

Blood lipid profile and myocardial superoxide dismutase in swim-trained young and middle-aged rats: comparison between left and right ventricular adaptations to oxidative stress - T. Ravi Kiran; M. V. V. Subramanyam; S. Prathima; S. Asha Devi (Journal of Comparative Physiology B, 2006)

Biodiversity Conservation in Sacred Groves of Manipur, Northeast India: Population Structure and Regeneration Status of Woody Species - Ashalata Devi Khumbongmayum; M. L. Khan; R. S. Tripathi (Biodiversity and Conservation, 2006)

Sacred groves of Manipur, northeast India:biodiversity value, status and strategies for their conservation - Ashalata Devi Khumbongmayum; M. L. Khan; R. S. Tripathi (Biodiversity and Conservation, 2005)

Effect of histone H1 on estrogen receptor status of human breast cancer MCF 7 cells - G. Vani; C. S. Shyamala Devi (Molecular and Cellular Biochemistry, 2005)

Barley-based medium for the cost-effective production of Bacillus thuringiensis - P. S. Vimala Devi; T. Ravinder; C. Jaidev (World Journal of Microbiology and Biotechnology, 2005)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

Cholinesterase Activity in Clam Meretrix casta: Possible Biomarker for Organophosphate Pesticide Pollution - K. P. Devi; S. K. Pandian; N. S. S. Kumar (Bulletin of Environmental Contamination and Toxicology, 2005)

Effect of arogh—A polyherbal formulation on the marker enzymes in isoproterenol induced myocardial injury - S. Suchalatha; C. S. Shyamala Devi (Indian Journal of Clinical Biochemistry, 2004)

Antioxidant effect of methanolic extract ofSolanum nigrum berries on aspirin induced gastric mucosal injury - Mallika Jainu; C. S. Shyamala Devi (Indian Journal of Clinical Biochemistry, 2004)

An efficient protocol for shoot regeneration and genetic transformation of pigeonpea [Cajanus cajan (L.) Millsp.] using leaf explants - S. Dayal; M. Lavanya; P. Devi; K. K. Sharma (Plant Cell Reports, 2003)

Temperature-induced changes in anaerobic capacity of interventricular septum in trained young and middle-aged rats - S. Asha Devi; A.B. Jolitha; S. Prathima (Biogerontology, 2002)

Plant regeneration from scutella of immature embryos of diverse sorghum genotypes - R. V. Sairam; N. Seetharama; T. Shyamala; P. S. Devi (Cereal Research Communications, 2000)

Culture and regeneration of mesophyll-derived protoplasts of sorghum [ Sorghum bicolor (L.) Moench] - R. V. Sairam; N. Seetharama; P. S. Devi; A. Verma; U. R. Murthy; I. Potrykus (Plant Cell Reports, 1999)

Microprojectile-mediated transient and integrative transformation of rice embryogenic suspension cells: effects of osmotic cell conditioning and of the physical configuration of plasmid DNA - Y. L. Nandadeva; C. G. Lupi; C. S. Meyer; P. S. Devi; I. Potrykus; R. Bilang (Plant Cell Reports, 1999)

Evaluation of marking and tagging methods for genetic studies in carp - Y. Basavaraju; B. S. Renuka Devi; G. Mukhatyakka; L. Purushotham Reddy; G. C. Mair; E. E. Roderick; D. J. Penman (Journal of Biosciences, 1998)

Nitrous oxide emissions under different soil and land management conditions - C. Henault; X. Devis; S. Page; E. Justes; R. Reau; J. C. Germon (Biology and Fertility of Soils, 1998)